Adoption pathways for new agricultural technologies: An approach and an application to Vertisol management technology in Ethiopia - Jabbar, M.A.; Beyene, H.; Mohamed-Saleem, M.A.; Gebreselassie, S. (International Livestock Research Institute, 1998)
The literature on technology adoption distinguishes between diffusion (generally viewed as a dynamic process) and adoption (usually seen as static and specific to a point in time). Consistent with this, empirical studies on agricultural technology adoption generally divide a population into adopters and non-adopters, and analyse the reasons for adoption and non-adoption at a point in time, principally in terms of the socio-economic characteristics of the studied population. This study discusses the deficiencies of static approaches to technology adoption, particularly at the early stages of diffusion. It proposes a dynamic approach to technology adoption in which information gathering, learning and experience play pivotal roles. The characteristics of both the user and the technology are considered important in explaining adoption behaviour and the resultant pathway of adoption. The proposed approach has implications for the time frame and potential impact of new technology adoption.